2014
DOI: 10.1016/j.jmb.2014.07.017
|View full text |Cite
|
Sign up to set email alerts
|

Control of RecBCD Enzyme Activity by DNA Binding- and Chi Hotspot-Dependent Conformational Changes

Abstract: Faithful repair of DNA double-strand breaks by homologous recombination is crucial to maintain functional genomes. The major Escherichia coli pathway of DNA break repair requires RecBCD enzyme, a complex protein machine with multiple activities. Upon encountering a Chi recombination hotspot (5′ GCTGGTGG 3′) during DNA unwinding, RecBCD’s unwinding, nuclease, and RecA-loading activities change dramatically, but the physical basis for these changes is unknown. Here, we identify, during RecBCD’s DNA unwinding, tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
55
1
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(61 citation statements)
references
References 51 publications
4
55
1
1
Order By: Relevance
“…Hence, both of these situations may mimic aspects of RecBCD after chi recognition. There have been suggestions that the RecB nuclease domain becomes repositioned after RecBCD recognizes a chi site[7, 58, 59]. In particular, the nuclease domain is involved in loading of RecA onto unwound ssDNA by directly binding to RecA[58].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, both of these situations may mimic aspects of RecBCD after chi recognition. There have been suggestions that the RecB nuclease domain becomes repositioned after RecBCD recognizes a chi site[7, 58, 59]. In particular, the nuclease domain is involved in loading of RecA onto unwound ssDNA by directly binding to RecA[58].…”
Section: Discussionmentioning
confidence: 99%
“…Hence, the nuclease domain would need to move from its position in the crystal structure in order to interact with RecA[58]. Recently, Taylor et al[59] also presented evidence for a conformational change upon chi recognition that involves movement of the nuclease domain.…”
Section: Discussionmentioning
confidence: 99%
“…The molecular basis for this intriguing result remains obscure. However, since the RecB nuclease domain is attached to the RecB motor by a long (≈70 amino acid) tether, and there is good evidence that the nuclease domain must detach from the position that it occupies in a crystal structure, there are many interesting possibilities that need to be tested.…”
Section: The Recb Arm May Function As a Double Stranded Dna Translocasementioning
confidence: 99%
“…We also showed that the secondary translocase of RecBC is not altered by chi recognition. Structural studies suggest that chi recognition induced nuclease domain movement, which consequently changes the degradation polarity and the ssDNA translocase activity of RecD …”
Section: Resultsmentioning
confidence: 99%
“…[4,5] Chi sequence thus allows RecBCD to discriminate the genome DNA of E. coli from foreign DNAs, as E. coli encoded thousands of copies of chi in its genome. [6,7] Upon chi recognition,R ecBCDs tarts to generate al ong3 ' ssDNA overhang terminiatedb yc hi and loads RecA to form an ucleoprotein filament in order to promote the homologousr ecombination. [8,9] The degradation preference of nucleased omain also shifts from 3'-strand to 5'-strand upon chi recognition.D egraded DNA fragments before chi recogni-tion is proposed as the substrates for Cas1-Cas2 complex, and is recently suggestedt ob ep reserved for future recognition of foreign DNA.…”
Section: Introductionmentioning
confidence: 99%